INFLUENCE GIVING OF EXTRACT FRUIT MENGKUDU TO HISTOPATOLOGI TESTIS WHITE MOUSE FOLLOWING AN INHALATION CIGARETTE SMOKE - S. D., Endah Rita (BIOMA, 2011)
This Research to know influence giving of extract fruit Mengkudu (Morinda citrifolia) to histopatologi of white mouse (Rattus norvegicus) testis following an inhalation cigarette smoke and to know how much is giving of extract fruit of Mengkudu more having an effect on in an optimal fashion for the minimization of to damage of testicle seminiferus tubulus white mouse given by wistar galur cigarette smoke treatmen.Eksperiment design in this research use completely random design (RAL) by four treatment that is (A) mouse + cigarette smoke + 0 ml / fruit extract day of Mengkudu as control; (B) mouse + cigarette smoke + 0,9 ml / fruit extract day of Mengkudu; ( C) mouse + cigarette smoke + 1,8 ml / fruit extract day of Mengkudu; (D). mouse + cigarette smoke + 2,7 ml / fruit extract day of Mengkudu, by four replication. Para-meter the measured white mouse testis seminiferus tubulus histopatologi. Research executed by UNNES in January 2011 until March 2011.Result of research indicate that treatment of fruit extract of mengkudu give influence which signifikan ( p< 0,05) to white mouse testis seminiferus tubulus histopatologi of wistar galur. Usage of fruit extract of Mengkudu dose 1,8 ml / day optimal dose in minimization damage of white mouse testis seminiferus tubulus, following an inhalation cigarette smoke.From result of the research can be concluded that usage of fruit extract of Meng-kudu can minimization damage of white mouse testis seminiferus tubulus given by cigarette smoke treatmen. But antioksidan with excessive dose can turn into pro-oksidan so that earn damage watering down effect of free radical.Keywords : fruit extract of mengkudu, testis, histopatologi, cigarette smoke